Activating Lattice Oxygen in Perovskite Ferrite for Efficient and Stable Photothermal Dry Reforming of Methane - Li, Jilong; Zhao, Jiwu; Wang, Sibo; Peng, Kang-Shun; Su, Bo; Liu, Kunlong; Hung, Sung-Fu; Huang, Meirong; Zhang, Guigang; Zhang, Huabin; Wang, Xinchen (Journal of the American Chemical Society, 2025)
Lattice oxygen (LO)-mediated photothermal dry reforming of methane (DRM) presents a promising approach to syngas production. However, realizing high DRM efficiency and durability remains challenging due to the difficulty in activating LOs in catalysts. Herein, we demonstrate that partially substituting Fe sites in perovskite ferrite (LaFeO3) by Mn triggers LOs, bestowing the catalyst with superior activity and stability for photothermal DRM after modification with Ru. The Mn exchange induces a charge transfer from La to Mn, which combined with the incoming photoexcited electrons reconstructs the perovskite’s electronic structure, weakening the La–O–Mn bonds and facilitating the LO migration. Meanwhile, photogenerated holes migrate to surface LOs, further enhancing their reactivity to mediate DRM. Under light irradiation, the catalyst exhibits an outstanding syngas production rate (H2: 42.89 mol gRu –1 h–1, CO: 54.92 mol gRu –1 h–1) while stably operating over 150 h. It also achieves a methane turnover frequency of 0.9 s–1 and a light-to-chemical energy efficiency of 15.3%, setting a benchmark for light-driven DRM performance. This work underscores the significance of exact site doping in metal oxides to fine-tune LO activity, providing valuable guidance for fabricating efficient catalysts for solar-powered redox reactions proceeded via the light-supported Mars–van Krevelen mechanism.